The Effect of U-Slot Designs on The Performances of Microstrip Patch Antenna - Mohd Zain, Norlina; Zairil Muhammad Nor, Muhammad; Tarmizi Ali, Mohd; Nur Darina Ahmad, Nur; Mohd Hussain, Mashitah; Faiz Zainal Abidin, Amar (International Journal of Engineering and Technology, 2018)
Slotted techniques are widely used in to enhance the performances of microstrip patch antenna. This includes enhancing their return loss, VSWR, bandwidth, directivity and other more. In this paper, the effect of different U-slot on microstrip patch antenna performances  focusing on return loss, VSWR, bandwidth, directivity, radiation pattern and gain are highlighted. Cutting a U-shaped slot on the middle of  patch is used to bandwidth of antenna can be enhanced. The SMA or coaxial probe is used as a feeding to this structure. A parametric study has been carried out to investigate the effect of different SMA position on symmetric U-slot, the arm length of the U-slot, and the distance between feed point and arm U-slot. The optimized antenna shows operating frequency band ranges from 2.1 – 2.8 GHz. The microstrip patch antenna with U-slot was designed and simulated using CST Microwave Environment software. It can be concluded that the U-slotted microstrip patch antenna yields high bandwidth ranges from 2% - 3%.